Mechanosynthesis of Fullerotetrahydroquinolines by Copper-Mediated sp3 C–H Functionalization of N,N-Dimethylanilines with [60]Fullerene - Yang, Huan; Ye, Shi-Qi; Shao, Gang; Chen, Jun-Shen; Wang, Guan-Wu (Synlett, 2023)
An efficient mechanochemical copper-mediated coupling reaction of [60]fullerene with para- or meta-substituted N,N-dimethylanilines under solvent-free and ambient conditions has been developed. The present protocol provides N-methylfullerotetrahydroquinolines containing electron-withdrawing or electron-donating groups on the phenyl ring in a short reaction time and at room temperature. This reaction occurs through copper-mediated sp3 C–H functionalization of N,N-dimethylanilines under ball-milling conditions. In addition, a representative fullerotetrahydroquinoline has been applied in a perovskite solar cell device.
Keywords: fullerenes; mechanochemistry; green chemistry; radical reaction; copper catalysis; solar cell